South Asia Economic Focus, Spring 2018 : Jobless Growth? - World Bank (Washington, DC: World Bank, 2018)
South Asia is again the fastest growing region in the world. And growth should further strengthen to 7.1 percent on average in 2019-20, reflecting an improvement across most of the region. But are countries generating enough jobs? The demographic transition is swelling the ranks of the working-age population across most of South Asia. For this report, crucial information about employment in South Asia is extracted in a transparent and replicable way from over 60 surveys and censuses covering the period from 2001 onwards. The analysis of this information reveals that employment does respond to economic growth in the short term, implying that growth is not jobless. It also appears that countries in South Asia have created large numbers of jobs over the years. However, the nature of the jobs created is not fully encouraging, and the analysis shows that rapid growth alone will not be sufficient to bring South Asian employment rates to the levels observed elsewhere in the developing world. In addition to high growth, more and better jobs need to be created for every percentage point of growth. The results in this chapter call for better employment data, and for a focus on the economic policies that can boost job creation.